A114 QUALITY AND EFFICACY OF PERCUTANEOUS ENDOSCOPIC GASTROSTOMY: A RETROSPECTIVE CHART REVIEW STUDY. (21st February 2022) - Aljabri, R S; Kwan, P
Abstract: Background: Passage of food along the digestive tract can be compromised by a number of conditions. Nasogastric tube (NGT) feeding is used in these cases but prolonged use can lead to various complications. Percutaneous endoscopy gastrostomy (PEG) has been reported as an effective and safe alternative to NGT. Clinical efficacy and adverse events related to PEG insertion are largely dependent on post-procedure care. Aims: To assess the clinical significance of PEG tube insertion procedure and impact of post-procedure care and diet protocol on associated adverse events and success rate at two Canadian tertiary care units. Methods: The retrospective electronic chart review was conducted on all patients who underwent endoscopic PEG fixation or replacement procedure at University of British Columbia Gastroenterology clinic and Vancouver General hospital Endoscopy Unit from 1 st April 2020 to 31 st March 2021. Data related to patient demographics, indications for insertion, insertion technique, quality of PEG insertion protocol, antibiotic prophylaxis, success rate, and rate of PEG-related complications were collected and analysed. An evaluation protocol was devised to evaluate the impact of indication-based diet protocols on frequency of adverse events and success rate. Results are suggested to be analysed using SPSS v 2021 with significance threshold of P-value < 0.05. Results: 43 PEG insertion procedures were performed, of which 3 failed due to structural reasonsincluding post gastric sleeve surgery, small stomach and difficulty in finding transillumination point. 25 cases underwent PEG insertion endoscopically for the first time, and 14 required exchanges, of which 2 underwent non-endoscopic exchange. Of 37 patients who underwent endoscopic PEG insertion 18(48.64%) were males and 19(51.36%) were females. Acute infection was reported in 6(14%) and chronic infection in 4 patients (9.3%). Tube dislodgment was reported in 10(23%), peristomal leak in 4(9.3%), miinor bleeding in 3(6.9%), and post-operative granulation in 4(9%) procedures. The evaluation protocol divides patients into two groups: Group a included d subjects who would receive low-volume (≤150 mL/d) and Group b who would receive a high-volume (≥300 mL/d) of feeding formula. Conclusions: PEG tube insertion is a very successful procedure with high clinical significance and low complications rate at VGH and UBC. A follow-up plan is therefore being initiated to evaluate impact of feeding volumes on rate of success and adverse events. Combined, the previous studies, suggest that the high-feeding volumes can be safely administered to rapidly attain calorie targets to increase the procedure efficacy. . Funding Agencies: CAG